High Plasma Glucagon Levels Correlate with Waist-to-Hip Ratio, Suprailiac Skinfold Thickness, and Deep Subcutaneous Abdominal and Intraperitoneal Adipose Tissue Depots in Nonobese Asian Indian Males with Type 2 Diabetes in North India. (28th May 2017) - Anoop, Shajith; Misra, Anoop; Bhatt, Surya Prakash; Gulati, Seema; Mahajan, Harsh; Prabakaran, Gokulraj
Abstract : We aimed to correlate plasma glucagon levels with anthropometric measures and abdominal adipose tissue depots. Nonobese males (n = 81 ; BMI < 25 kg/m 2 ) with T2DM of less than one-year duration and nonobese males without diabetes (n = 30 ) were evaluated for the following: anthropometry (BMI, waist circumference, W-HR, and truncal skinfolds), whole-body DEXA (for body fat and fat-free mass), and MRI scan (for volumes of subcutaneous abdominal adipose tissue (SCAT) including superficial and deep, intra-abdominal visceral adipose tissue (including intraperitoneal adipose tissue (IPAT), retroperitoneal adipose tissue, liver span and fatty liver, and pancreatic volume)). Plasma glucose and glucagon, serum insulin, hepatic transaminases, and lipid profile were measured. Significantly higher levels of fasting and postprandial glucagon (p < 0.001 ) and fasting and postprandial insulin (p < 0.001 ) were seen in patients with T2DM. The mean values of fasting and postprandial plasma glucagon levels were higher in T2DM patients with NAFLD (n = 37 ) as compared to T2DM patients without NAFLD (n = 44 ). Four independent predictors were derived for fasting glucagon levels in patients with T2DM, namely, W-HR, suprailiac skinfold thickness, IPAT, and deep SCAT (p < 0.05 ; r 2 = 0.84 ). These observations in Asian Indians may have significance for diabetes therapies which impact glucagon levels.